Geometric characterization of soil structure through unconventional analytical tools - Tseng, Chien Ling; Alves, Marlene Cristina [UNESP]; Bastos Pereira Milor, Debora Marcondes; Crestana, Silvio (Elsevier B.V., 2018)
Soil structure is essential for soil function and environmental quality. Therefore, adequate evaluation of management systems is essential to ensure the preservation and regeneration of soil structure. Techniques such as X-ray microtomography and automated soil particle size analysis based on gamma-ray attenuation provide rapid quantification of soil physical properties and allow for the evaluation of soil structure. The aim of this study is to determine soil physical parameters using unconventional analytical tools to characterize and evaluate the geometric characteristics of soils with different structures at high accuracy. Soil samples extracted from the UNESP experimental farm (Brazil) were separated into two different management groups according to their textural similarity. The following results were obtained from the analysis: 1) Microtomography can be used to extract soil porosity, including soil microporosity. 2) The shape factor indicates the geometric organization of the soil structure, which is relevant and valid for evaluating the degree of soil degradation. 3) The fractal dimension is related to the soil particle and aggregate size distribution but was not sufficient for describing the soil geometric properties when used alone. 4) Coupling the fractal dimension with the lacunarity provides an important tool for estimating the soil structure. Finally, the application of the physical parameters from the unconventional method provided new insights for understanding soil geometric structure, which can support future investigations of flow phenomena in the soil.
Keywords: Microtomography; Porosity; Shape factor; Fractal dimension; Lacunarity; Tropical soil